Histological Analysis and Diagnosis of Dementia (Texas Journal of Medical Science, 2024)
Dementia is a widespread condition in the elderly, resulting from the damage and death of brain cells. One of the most common forms of this disease is Alzheimer's disease; however, other forms, including Lewy body dementia, frontotemporal dementia, and vascular dementia, also exist. These conditions exhibit various pathological changes in different areas of the brain, which reflect in the clinical symptoms of the disease. Histological analysis of dementia is one of the primary methods for understanding the disease, diagnosing it, and identifying its stages of progression. Through these analyses, the pathology of nerve cells, including neurofibrillary tangles, amyloid plaques, Lewy bodies, and other histological changes, is identified. These changes are associated with the damage to neurons and their connections, leading to cognitive and neurological dysfunctions